Priority Needs for Conducting Pandemic-relevant Clinical Research With Children in Europe: A Consensus Study With Pediatric Clinician-researchers. Issue 5 (May 2019) - Gal, Micaela; Gobat, Nina; Francis, Nicholas A.; Hood, Kerenza; Butler, Christopher C.; Bielicki, Julia; Fraaij, Pieter L.; Sharland, Mike; Jarvis, Jessica; van Rossum, Annemarie M. C.; Heikkinen, Terho; Martinon-Torres, Federico; et al.
Abstract : Background: Infectious disease (ID) pandemics pose a considerable global threat and can disproportionately affect vulnerable populations including children. Pediatric clinical research in pandemics is essential to improve children's healthcare and minimize risks of harm by interventions that lack an adequate evidence base for this population. The unique features of ID pandemics require consideration of special processes to facilitate clinical research. We aimed to obtain consensus on pediatric clinician-researchers' perceptions of the priorities to feasibly conduct clinical pediatric pandemic research in Europe. Methods: Mixed method study in 2 stages, recruiting pediatric clinician-researchers with experience of conducting pediatric ID research in clinical settings in Europe. Stage 1 was an expert stakeholder workshop and interviews. Discussions focused on participant's experience of conducting pediatric ID research and processes to facilitate pandemic research. Information informed stage 2, an online consensus survey to identify pediatric inician-researchers priorities to enable ID pandemic research. Results: Twenty-three pediatric clinician-researchers attended the workshop and 39 completed the survey. Priorities were primarily focused on structural and operational requirements of research design and regulation: (1) clarity within the European Clinical Trials Directive for pediatric pandemic research; (2) simplified regulatory processes for research involving clinical samples and data; and (3) improved relationships between regulatory bodies and researchers. Conclusions: Results suggest that changes need to be made to the current regulatory environment to facilitate and improve pediatric research in the pandemic context. These findings can provide expert evidence to research policy decision-makers and regulators and to develop a strategy to lobby for change. Abstract : Supplemental Digital Content is available in the text.